The Implementation of the Index Card Match (ICM) Strategy to Improve Learning Achievement in Tarkibul Jumal among Year 8A Students at MTsN 1 Madiun - Fuad L Anshori; Alif Cahya Setiyadi; Zaki Abdul Muhaimin (Universitas Muhammadiyah Sumatera Barat, 2026)
This study addresses students’ difficulties in understanding Arabic sentence structures (tarkibul jumal), which are often perceived as abstract and difficult to learn through conventional teaching methods. These challenges result in low student engagement and limited mastery of Arabic grammar in classroom learning. Therefore, this study aims to improve students’ understanding of tarkibul jumal and enhance the quality of Arabic language instruction through the implementation of the Index Card Match strategy. The study employed Classroom Action Research based on the Stephen Kemmis and Robin McTaggart model, conducted in two cycles with Year 8 students at MTsN 1 Madiun during the 2025–2026 academic year. The Index Card Match strategy encouraged students to actively participate through matching question-and-answer cards, discussion, collaboration, and interactive learning activities. The findings revealed a significant improvement in students’ learning outcomes, with the mean score increasing from 6.03 in the first cycle to 8.79 in the second cycle, and all students achieving mastery learning by the end of the study. In conclusion, the Index Card Match strategy proved effective in improving students’ comprehension of Arabic sentence structures and creating a more active and enjoyable Arabic learning environment.